TRANSMIGRASI DI OJS 3 LINK : https://jurnal2.untagsmg.ac.id/index.php/nlr - Setiyowati; Johan Erwin Isharyanto; Husnia Hilmi Wahyuni (Faculty of Law, Universitas Pekalongan, 2024)
The study examines the implementation of Law Number 41 of 2004 concerning Waqf in resolving disputes over the sale of waqf land in Kendayakan Village, Warureja District, Tegal Regency which causes legal and social conflicts because they conflict with the provisions of Article 40 of Law Number 41 of 2004 concerning Waqf, that waqf property that has been waqf is prohibited from being used as collateral, confiscated, donated, sold, inherited, exchanged or transferred in the form of other rights transfers. The approach method used is empirical juridical with interviews and literature studies. The results of the study indicate that one of the factors causing disputes over the sale of waqf land occurs because of the absence of Nazhir in managing the waqf land, so that the management of the waqf land is carried out by the administrators of the Mosque who are not actually Nazhir because there is no replacement Nadzir. The settlement of the waqf land sale dispute was carried out through deliberation by inviting related parties and attended by government institutions as mediators, but the management of the Mosque that had sold the waqf land until now has not implemented the joint decision that has been agreed to restore the function of the waqf land that has been bought and sold and asked to provide replacement land to residents who have bought the land, so that the litigation path is the solution being considered.